Adherence to lipid-lowering therapy and the use of preventive health services: an investigation of the healthy user effect - Brookhart, M Alan; Patrick, Amanda R; Dormuth, Colin; Avorn, Jerry; Shrank, William; Cadarette, Suzanne M; Solomon, Daniel H (American journal of epidemiology, 2007)
Patients who adhere to preventive therapies may be more likely to engage in a broad spectrum of behaviors consistent with a healthy lifestyle. Because many of these behaviors cannot be measured easily, observational studies of outcomes associated with the long-term use of preventive therapies are subject to the so-called "healthy user bias." To better understand this effect, the authors examined the association between adherence to statin therapy and the use of preventive health services in a Pennsylvania cohort of 20,783 new users of statins between 1996 and 2004. After adjustment for age, gender, and various comorbid conditions, patients who filled two or more prescriptions for a statin during a 1-year ascertainment period were more likely than patients who filled only one prescription to receive prostate-specific antigen tests (hazard ratio (HR)=1.57, 95% confidence interval (CI): 1.17, 2.19), fecal occult blood tests (HR=1.31, 95% CI: 1.12, 1.53), screening mammograms (HR=1.22, 95% CI: 1.09, 1.38), influenza vaccinations (HR=1.21, 95% CI: 1.12, 1.31), and pneumococcal vaccinations (HR=1.46, 95% CI: 1.17, 1.83) during follow-up. These results suggest that patients who adhere to chronic therapies are more likely to seek out preventive health services, such as screening tests and vaccinations. Further work is needed to identify study design and analysis methods that can be used to minimize the healthy user bias in studies of preventive therapies.